Pemanfaatan Limbah Cair Pabrik Pengolahan Kelapa Sawit Sebagai Perekat Pada Pembuatan Briket Dari Arang Pelepah Kelapa Sawit (Elaeis Guineensis Jacq) - Sitanggang, Hendri Manogu Pranata; Romy, Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Waste of fronds is solid palm oil waste generated from palm oil plantations. To increase the value added, then this waste can be utilized as charcoal briquettes that can be used as an alternative energy source. The purpose of this study were (1) to know proximasi briquettes from palm fronds with adhesive wastewater CPO (Crude Palm Oil), (2) determine the resistance (durability) briquettes palm fronds with CPO adhesive liquid waste, (3) determine the calorific value contained in briquettes midrib palm oil CPO adhesive liquid waste, (4) determine the length of time the use of briquettes in water heating compared with a stove. This study used an experimental method, the object is to use waste oil palm fronds which uses wastewater from the processing of the PKS as an adhesive. By comparison wastewater PKS and palm fronds charcoal that is 30%: 70%, 35%: 65%, 40%: 60%, 45%: 55%, 50%: 50%, 55%: 45%, 60%: 40%, 65%, 35% and 70%: 30%. Based on the research results, obtained the best calorific value contained in the particle size of 50 mesh with the average value of 29176,921 J / g.Keywords: Waste oil palm fronds, charcoal briquettes, endurance (durability), calorific value.